2001
DOI: 10.1046/j.1365-2885.2001.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of sarafloxacin in pigs and broilers following intravenous, intramuscular, and oral single‐dose applications

Abstract: Pharmacokinetics of sarafloxacin, a fluoroquinolone antibiotic, was determined in pigs and broilers after intravenous (i.v.), intramuscular (i.m.), or oral (p.o.) administration at a single dose of 5 (pigs) or 10 mg/kg (broilers). Plasma concentration profiles were analysed by a noncompartmental pharmacokinetic method. Following i.v., i.m. and p.o. doses, the elimination half-lives (t1/2beta) were 3.37 +/- 0.46, 4.66 +/- 1.34, 7.20 +/- 1.92 (pigs) and 2.53 +/- 0.82, 6.81 +/- 2.04, 3.89 +/- 1.19 h (broilers), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…administration was superior to p.o. administration of sarafloxacin in pigs (Ding et al ., 2001), danofloxacin in cattle and swine (Mann & Frame, 1992) and for enrofloxacin in broiler chickens (Bugyei et al ., 1999), calves and piglets (Scheer, 1988), homing‐pigeons (Dorrenstein & Verburg, 1988), chickens (Abd‐El‐Aziz et al ., 1997) and ducks (Intorre et al ., 1997). Only one study described faster absorption and higher C max after p.o.…”
Section: Discussionmentioning
confidence: 99%
“…administration was superior to p.o. administration of sarafloxacin in pigs (Ding et al ., 2001), danofloxacin in cattle and swine (Mann & Frame, 1992) and for enrofloxacin in broiler chickens (Bugyei et al ., 1999), calves and piglets (Scheer, 1988), homing‐pigeons (Dorrenstein & Verburg, 1988), chickens (Abd‐El‐Aziz et al ., 1997) and ducks (Intorre et al ., 1997). Only one study described faster absorption and higher C max after p.o.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 This small volume of distribution indicates that ciprofloxacin was not well distributed into tissue after po administration in broiler. Maximum concentration, 0.26 ± 0.03 mg l À1 , after po administration of ciprofloxacin in this study was observed at 4.40±0.1 h. which is much higher than sarafloxacin, enrofloxacin, danofloxacin 13,17,19 and ciprofloxacin. 8,20 This higher value indicates that ciprofloxacin reached slowly to its peak concentration than sarafloxacin, enrofloxaci, danofloxacin and ofloxacin after po administration in broiler.…”
Section: Discussionmentioning
confidence: 41%
“…14 The plasma half-life, t ½ , after oral administration in broiler was estimated to be 5.25 ± 0.02 h, much higher than i.v. administration of ciprofloxacin and enrofloxacin 15,16 and oral administration of sarafloxacin, 13 but apparently shorter than oral administration of danofloxacin and enrofloxacin. 17,18 This value is almost same to po administration of ofloxacin in broiler.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations